1990
DOI: 10.1111/j.1349-7006.1990.tb02500.x
|View full text |Cite
|
Sign up to set email alerts
|

Carcinogenicity of 2‐Amino‐3‐methylimidazo[4,5‐f]quinoline in Nonhuman Primates: Induction of Tumors in Three Macaques

Abstract: The carcinogenic potential of 2‐amino‐3‐methylimidazo[4,5f]quinoline (IQ) was evaluated in cynomolgus monkeys. Monkeys received IQ, beginning at the age of one year, at doses of 10 or 20 mg/kg by gavage. Thus far, IQ has induced hepatocellular carcinoma in three monkeys with a latent period of 27 to 37 months. Metastases to the lung occurred in two of the three monkeys. Microscopically, the hepatocellular carcinoma in all three cases demonstrated a trabecular pattern. These data demonstrate that IQ is a potent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
118
0

Year Published

1994
1994
2008
2008

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 219 publications
(120 citation statements)
references
References 5 publications
2
118
0
Order By: Relevance
“…These compounds can react together during cooking at high temperatures in Maillard reactions (Jägerstad et al, 1983). The carcinogenicity of different members of the HCA family has been proven in animal models (Adamson et al, 1990;Shirai et al, 1995). However, recent epidemiological studies concerning HCA intake gave conflicting results.…”
Section: Introductionmentioning
confidence: 99%
“…These compounds can react together during cooking at high temperatures in Maillard reactions (Jägerstad et al, 1983). The carcinogenicity of different members of the HCA family has been proven in animal models (Adamson et al, 1990;Shirai et al, 1995). However, recent epidemiological studies concerning HCA intake gave conflicting results.…”
Section: Introductionmentioning
confidence: 99%
“…© Oxford University Press azo [4,5-/]quinoline (IQ) also positive in primates (8). Epidemiological studies have shown a relationship between the consumption of fried meat products and an elevated risk of colon and other cancers (9)(10)(11)(12)(13).…”
Section: Introductionmentioning
confidence: 99%
“…(30) In these animals, N-hydroxylation, subsequent adduct formation and probable carcinogenesis of IQ appears to be largely dependent on hepatic CYP3A4 and/or CYP2C9/10 (31) and not CYP1A2 having high specificity and catalytic activity for IQ, (32) which is not expressed in liver of this species.…”
Section: Discussionmentioning
confidence: 99%